2020
DOI: 10.1111/sms.13903
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eHealth to increase physical activity in healthy adults over 55 years: A systematic review and meta‐analysis

Abstract: To estimate the effect of eHealth interventions on increasing physical activity (PA) in healthy adults over 55 years, a systematic review and meta‐analysis was conducted following the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis (PRISMA) guidelines. MEDLINE, Cochrane, Web of Science, SPORTDiscus, and Scopus databases were searched, from inception to February 2020, for experimental studies reporting the effect of eHealth interventions on steps/day, daily moderate‐to‐vigorous physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 53 publications
(58 reference statements)
4
20
2
1
Order By: Relevance
“…Compared with previous research suggesting that eHealth interventions can effectively promote PA in older adults in the short term [ 1 , 11 - 13 , 50 - 53 ], we were not able to demonstrate intervention effects for participants in the WEB and WEB+ conditions, neither in the short term at 3 months nor in the longer term at 9 months. This is puzzling, as several recently published systematic reviews and meta-analyses [ 50 - 53 ] demonstrate the effectiveness of eHealth interventions, including mobile interventions [ 52 ], for improving PA levels (eg, mean steps per day and minutes of daily MVPA, weekly PA, and MVPA [ 50 ]) in predominantly healthy older adults. Similar to our study, acceptance of eHealth intervention approaches was high in the studies included in these systematic reviews and meta-analyses [ 50 ]; however, contrary to our attrition rate, studies included in [ 50 ] predominantly reported attrition below 20% [ 50 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Compared with previous research suggesting that eHealth interventions can effectively promote PA in older adults in the short term [ 1 , 11 - 13 , 50 - 53 ], we were not able to demonstrate intervention effects for participants in the WEB and WEB+ conditions, neither in the short term at 3 months nor in the longer term at 9 months. This is puzzling, as several recently published systematic reviews and meta-analyses [ 50 - 53 ] demonstrate the effectiveness of eHealth interventions, including mobile interventions [ 52 ], for improving PA levels (eg, mean steps per day and minutes of daily MVPA, weekly PA, and MVPA [ 50 ]) in predominantly healthy older adults. Similar to our study, acceptance of eHealth intervention approaches was high in the studies included in these systematic reviews and meta-analyses [ 50 ]; however, contrary to our attrition rate, studies included in [ 50 ] predominantly reported attrition below 20% [ 50 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This is puzzling, as several recently published systematic reviews and meta-analyses [ 50 - 53 ] demonstrate the effectiveness of eHealth interventions, including mobile interventions [ 52 ], for improving PA levels (eg, mean steps per day and minutes of daily MVPA, weekly PA, and MVPA [ 50 ]) in predominantly healthy older adults. Similar to our study, acceptance of eHealth intervention approaches was high in the studies included in these systematic reviews and meta-analyses [ 50 ]; however, contrary to our attrition rate, studies included in [ 50 ] predominantly reported attrition below 20% [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a new scoping review is required to more broadly identify any available digital technologies that target any aspects of healthy aging in nonclinical settings (ie, daily life). [22] Physical activity, diet, quality of life, and well-being eHealth 50+ Buyl et al, 2020 [23] Physical activity eHealth 50+ Kwan et al, 2020 [24] Physical activity mHealth a and eHealth 50+ McGarrigle et al, 2020 [25] Physical activity, healthy eating, stress management, and tobacco cessation Digital coaching 50+ Stara et al, 2020 [26] Walking Exergaming 60+ Janhunen et al, 2021 [27] Physical activity eHealth 55+ Nunez de Arenas-Arroyo et al, 2021 [28] a mHealth: mobile health.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, several systematic reviews show that eHealth interventions (such as interactive websites, smartphone applications, etc.) are effective in increasing PA levels in adults aged over 50 years [53,54]. The barriers that have been found to promote active aging have been described as a lack of time, organizational restrictions, limitations of being referred to adequate services, a lack of interest and support in prevention by administrators, a lack of incentives to participate, a lack of financial resources, too few personnel, and a lack of transportation, among others [5].…”
Section: Discussionmentioning
confidence: 99%